Multidirectional insights on Chrysophyllum perpulchrum leaves and stem bark extracts: HPLC-ESI-MSn profiles, antioxidant, enzyme inhibitory, antimicrobial and cytotoxic properties - Baloglu, Mehmet Cengiz; Llorent-Martínez, Eulogio J.; Aumeeruddy, Muhammad Zakariyyah; Mahomoodally, Mohamad Fawzi; Altunoglu, Yasemin Celik; Ustaoglu, Buket; Ocal, Mustafa; Gürel, Songül; Bene, Kouadio; Sinan, Kouadio Ibrahime; Zengin, Gokhan (Elsevier BV, 2019)
Abstract Chrysophyllum perpulchrum Mildbr. ex Hutch. & Dalziel has been reported to possess several therapeutic properties in African traditional medicine. However, its pharmacological properties have not been fully studied. Herein, we focused on the evaluation of the antioxidant, enzyme inhibitory, antimicrobial and cytotoxic effects of three solvent extracts (ethyl acetate, methanol, and water) of the stem bark and leaves. Polyphenolic components of the extracts were also identified by high-performance liquid chromatography with electrospray ionization mass spectrometric detection (HPLC-ESI-MSn). The methanolic stem bark extract possess the highest DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging, ferric and molybdenum (VI) reducing, and the highest inhibitory effect against acetylcholinesterase and butyrylcholinesterase. The aqueous stem bark extract displayed the highest ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)) scavenging and cupric reducing power. In contrast, the leaf ethyl acetate extract was the most effective metal chelator and α-amylase inhibitor while the leaf methanolic extract exhibited the highest tyrosinase and α-glucosidase inhibition. The highest total phenolic content (131.58 mg GAE/g extract) was recorded from the methanolic stem bark extract while the leaf methanolic extract was the richest in total flavonoid content (30.43 mg RE/g extract). Flavan-3-ols were main group in the methanol extracts. The minimum inhibitiory concentration values for the methanolic stem bark extract against Gram positive and negative bacteria strains ranged between 62.5–125 μg/ml. Bark extracts of C. perpulchrum were very effective against Salmonella kentucky, Proteus vulgaris and Staphylococcus aureus at 62.5 μg/ml. In addition, cytotoxic activity of stem bark samples was evident at lower concentration than those of leaf extracts. Stem bark extracts displayed the highest prevention against to HeLa cell line (IC50 = 264 μg/mL after 48 h). In light of the above, C. perpulchrum might provide health benefits against oxidative stress and the associated chronic diseases. Nonetheless, the detailed mechanism of action is yet to be further investigated.
Keywords: Enzyme inhibition; Anticancer; Enzyme Inhibition; Africa; Polyphenolic; Antimicrobial; Antioxidant; 6. Clean water; 3. Good health